Solving Problematic Financing Through the Execution of Murabaha Contracts: A Case Study of Agam Madani BMT - Arwanto, Alfin Dani; Arianti, Farida; Putri Z, Wina Antika; Yani, Suci Fitri; Leli, Maisarah; Rizal, Deri (Universitas Alma Ata, 2023)
Murabahah is one of the contracts and products at BMT Agam Madani. This product is financing that is in great demand and is liked by the public. Murbahah contracts cannot be avoided when problematic financing occurs which is favored by interested parties from the community indirectly and contains risks. This study aims to describe the use of the execution method to overcome problematic financing in Murabaha contracts. The method used is a qualitative method with a case study approach. The source of data is done by looking at the social situation regarding problematic financing to the point of saturation. Data collection techniques were carried out using in-depth interviews, namely interview guides aimed at customer informants and BMT employees, besides that they also made observations. The results found from the research that the settlement of problematic financing at BMT Agam Madani is classified into two forms, if there is good faith from the customer, then a rescheduling is carried out. If the customer is not good enough, a warning letter will be given up to three times and ends with execution in the form of submitting debt guarantees. This is done because the letter of guarantee signed by the parties is entered into as a deed of acknowledgment of debt which is classified as an authentic deed and execution as an execution of the payment of a sum of money.